PENGARUH UKURAN PERUSAHAAN, STRUKTUR AKTIVA DAN PROFITABILITAS TERHADAP STRUKTUR MODAL - Ichwan, Fith yuniar; Widyawati, Dini (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The use of own capital will be the burden to the total risk of the company and it becomes assurance for the creditors. Meanwhile, foreign capital is a capital which comes from the creditor and it is an account receivable for the related company. The purpose of this research is to find out the influence of firm size, asset structure, and profitability to the capital structure on automotive companies which are listed in Indonesia Stock Exchange. The samples are 10 automotive companies which are listed in Indonesia Stock Exchange (IDX) and quantitative is the method which used in this research, the data is the secondary data which is in the form of audit financial statement. The quantitative research method is used as the data analysis technique which is done by performing descriptive research, meanwhile the multiple linear regressions is used as the analysis technique. The result of the research shows that the coefficient determination value is 37.8% and each of asset structure, firm size, and profitability variable has significant influence to the capital structure. Meanwhile, 62.2% of the disclosure of capital structure can be explained by the others variable outside of this research model. The result of hypothesis test is the influence of asset structure, firm size and profitability variables which have positive influence to the capital structure with its significance value is less than Î± (0.05).Keywords: Firm Size, Asset Structure, Profitability, and Capital Structure.